Study on the wave impact forces below the deck of multi‐column offshore floating structures - Tay, Keng Kai. (2012)
The introduction of the Semi-Submersible floating platform into the offshore industry has allowed man to go ever-increasing depth in search of oil. However as these floating platform moves into ever deeper water, they are required to face much stronger weather and wave conditions. The study of the airgap issues is find the most effective way to determine the minimum required height for the lower deck of Semi-Submersible floating platform. This report uses a computer model simulation program, ANSYS, to model on the lower half of semi-submersible. The models will be put into the ANSYS hydrodynamic computer simulation, AQWA, which will focus on the effect of the different draft heights, type of wave forces and weather conditions that will have on the minimum required airgap height. Wave’s forces include incident, diffraction, radiation and all second order term. Weather conditions will concentrate on the different wave significant height and the peak frequency. The results produced from the computer simulation program were plotted into table and graphs and discussed in this report.